An Ecosystem Approach for understanding status and changes of Nador lagoon (Morocco): application of food web models and ecosystem indices. (20th March 2016) - Bocci, M.; Brigolin, D.; Pranovi, F.; Najih, M.; Nachite, D.; Pastres, R.
Abstract: The work applies food web models to the Lagoon of Nador (Morocco) and subsequently estimates ecosystem indices. This effort supports the evaluation of the ecosystem status and the implementation of the Ecosystem Approach (EcAp), endorsed by the contracting parties of the Barcelona Convention for the Mediterranean Sea. The Lagoon of Nador, on the Mediterranean coast of Morocco, suffered from eutrophication during recent decades. We used indices derived from Ecological Network Analysis for investigating the most relevant features of ecosystem functioning in the decade 2000−2010 ( present scenario ), and comparing them with those of the 1980s ( past scenario ). As the Lagoon includes different habitats, the methodology was applied to each of them, in order to assess their contribution to the functioning of the whole ecosystem. Results highlighted an increase in Total System Throughput (TST) in the present scenario when compared with the past one, also associated to an increase of Total Respiration (TR) and of the ratio between Total Primary Production and Total Respiration (TPP/TR). Under the present scenario Nador lagoon shows a decreased cycling efficiency. The sensitivity analysis highlighted the capability of TST and Comprehensive Cycling Index (CCI) in detecting changes, in agreement with other recent studies on responses of food web functioning to eutrophication. The results are discussed in respect to three specific aspects, related with the application of food Web Models and Ecological Network Analysis in the EcAp context: i) data availability; ii) spatialization of indicators; iii) selected set of indicators. The results also highlight the important role of sensitivity/uncertainty analysis when implementing food web models in data-scarce systems.